The clinical efficacy of intravascular laser irradiation of blood (ILIB): A narrative review of randomized controlled trial - Leonardo Díaz; Alain Chaple Gil; Alfredo Von Marttens; Javier Basualdo; Claudio Sotomayor; Alexis Vera Becerra; Víctor Beltrán; Gilbert Jorquera; Rodrigo Caviedes; Eduardo Fernández (Photodiagnosis and Photodynamic Therapy)
Background: Intravascular Laser Irradiation of Blood (ILIB) is a systemic application of photobiomodulation therapy (PBMT), proposed to modulate oxidative stress, inflammation, and mitochondrial function. Although its clinical use is expanding across various medical conditions, a consolidated evaluation of its therapeutic relevance remains lacking. Objective: This review aimed to synthesize available evidence from randomized controlled trials (RCTs) on the clinical efficacy and safety of ILIB, with particular focus on outcomes related to pain, inflammation, oxidative stress, and quality of life. Methods: a narrative literature review guided by PRISMA principles and the PROPS contextual framework. Eight RCTs involving 340 participants were identified through searches in five electronic databases and gray literature. Studies were eligible if they investigated ILIB—via intravascular or transcutaneous application—and reported clinical or biochemical outcomes compared to sham, placebo, or standard care. Results: Eight RCTs comprising 340 participants were included, addressing conditions such as cardiovascular disease, diabetic neuropathy, osteoarthritis, spinal cord injury, chronic endometritis, cellulite, and pediatric dental anxiety. ILIB demonstrated consistent reductions in pain (30–55 %), inflammatory cytokines (e.g., IL-6, TNF-α), and oxidative stress markers, along with significant improvements in mitochondrial activity and quality-of-life indicators (SF-36, WOMAC). No serious adverse events were reported. RoB analysis indicated four studies with low risk and four with some concerns. Conclusions: ILIB appears to be a safe and promising intervention with systemic biological effects and multidimensional clinical benefits. Future clinical research should prioritize standardized dosimetry protocols and long-term, patient-centered outcomes to guide broader integration into evidence-based care.